Resistivity of graphene/silver hybridization conductive ink on bending test - Salim, Mohd Azli; Ismail, Ismaniza; Masripan, Nor Azmmi; Md. Saad, Adzni; Akop, Mohd Zaid; Chew, Kit Wayn; Photong, Chonlatee (Semarak Ilmu Publishing, 2024)
In recent years, there has been a growing demand for stretchable electronic devices, such as wearable sensors and displays. Many researchers have been working on the development of stretchable conductive ink (SCI), which can maintain its electrical conductivity even when stretched or deformed. Graphene nanoplatelet (GNP) hybridization conductive ink is a promising material for stretchable electronics due to its high electrical conductivity and excellent mechanical properties. However, the resistivity of GNP ink on flexible substrates can be affected by various factors, such as the bending of the substrate. This paper aims to investigate the resistivity of hybridization conductive ink between GNP and silver (Ag) on a flexible substrate under different bending conditions. The study was carried out on the formulation and performance of GNP hybrids using GNP and silver flakes (Ag). The GNP hybrid ink was printed on a copper substrate using a mesh stencil method and cured at 250 °C for an hour. The resistivity was evaluated at room temperature before and after the bending tests in terms of electrical characteristics. The result of the resistivity value before performing the bending test was acceptable due to the lowest resistivity value in the range of 0.963 x 10–5 to 1.293 x 10–5 Ω.m at room temperature. The finding exposed that the resistivity values for each of the three samples of bending tests significantly changed after 1000 cycles. Overall, the results revealed that this hybrid conductive ink has good resistivity and performs with acceptable reliability. In future work, it is recommended that the conductive ink be printed on a more flexible substrate and the evaluation of temperature dependence can also be made more comprehensively.